A Simple Incentive Compatible Scheme for Attaining Lindahl Allocations - Walker, Mark (Econometrica, 1981)
[A simple scheme for making governmental decisions about the production and financing of public goods is presented. The "competitive" equilibria under the scheme are Pareto optimal; more importantly, they are Lindahl equilibria. Thus, it is never in any individual's interest to refuse to participate (no one will be worse off at the equilibrium than at his initial holding); moreover, the existence of equilibria is assured in the usual classical public-goods economies.]